Pengaruh Promosi melalui Media Sosial Instagram terhadap Peningkatan Penjualan di Raniapetshop - Shafa Rania Kamila; Albari Albari (ManBiz: Journal of Management and Business, 2024)
This study aims to determine the effect of Instagram social media promotion on increasing sales at Raniapetshop. In this study, researchers used a quantitative approach with sampling by filling out a questionnaire on google form. The use of descriptive analysis methods processed using SPSS software as many as 70 respondents. The results of this study indicate that the promotion variable has no positive and significant effect on increasing sales. The social media variable has a positive effect on increasing sales. After this research is conducted, it will then be used by Raniapetshop as a reference for the future in promotional activities on Instagram social media, to be able to facilitate the delivery of information with Instagram content and interact with consumers so that later it will encourage consumers to interact with other consumers and can encourage increased sales at Raniapetshop. It is also expected that further research can develop the current model with the addition of variables or may use the current model but with a different concept.